2016
DOI: 10.1080/19443994.2014.988657
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of anthraquinonic dye in water by photoactivated periodate

Abstract: In this work, the degradation of Acid blue 25 (AB25), an anthraquinonic dye and a widely used colorant in many industries, by photoactivated periodate (UV/IO À 4 ) process was investigated. Experiments were conducted in batch mode using a low-pressure mercury lamp emitting mainly at 253.7 nm. The effects of the operational conditions such as periodate ions concentration, initial dye concentration, initial pH of the solution, and tert-butanol addition on the degradation of AB25 were examined. The results have s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…PI activation techniques is an ongoing area of research and innovation. PI can be activated by different methods; the most known of them are UV radiation, 15–19 alkali, 20 ultrasound, 21,22 and transition metals 17,23 . Granular activated carbon (alone or doped with iodine), Co/N‐doped graphene, and Fe, N‐doped carbonaceous are among other developed catalytic techniques for efficient PI activation for organic destruction 24–26 .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…PI activation techniques is an ongoing area of research and innovation. PI can be activated by different methods; the most known of them are UV radiation, 15–19 alkali, 20 ultrasound, 21,22 and transition metals 17,23 . Granular activated carbon (alone or doped with iodine), Co/N‐doped graphene, and Fe, N‐doped carbonaceous are among other developed catalytic techniques for efficient PI activation for organic destruction 24–26 .…”
Section: Introductionmentioning
confidence: 99%
“…The study showed that various ROS, including • OH, HO 2 • and 1 O 2 , are the primary oxidants in the PI/HA system. Although IO 3 • has been identified as the primary reactive species in several PI‐based AOPs, 15–19,21,24,26 no evidence of IO 3 • production was observed in the PI/HA system 31 . Tert‐butyl‐alcohol (TBA) was used as a scavenger to test IO 3 • production since it is unreactive with IO 3 • .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations